Overexpression of a pathogenesis-related gene NbHIN1 confers resistance to Tobacco Mosaic Virus in Nicotiana benthamiana by potentially activating the jasmonic acid signaling pathway. (June 2019) - Peng, Haoran; Pu, Yundan; Yang, Xue; Wu, Gentu; Qing, Ling; Ma, Lisong; Sun, Xianchao
Highlights: NbHIN1 protein localizes in the plasma membrane and cytosol. Overexpression of NbHIN1 enhances the resistance to TMV. Overexpression of NbHIN1 highly regulates the expression of NbRAB11 . Abstract: Harpin proteins secreted by plant-pathogenic gram-negative bacteria induce diverse plant defenses against different pathogens. Harpin-induced 1 ( HIN1 ) gene highly induced in tobacco after application of Harpin protein is involved in a common plant defense pathway. However, the role of HIN1 against Tobacco mosaic virus (TMV) remains unknown. In this study, we functionally characterized the Nicotiana benthamiana HIN1 ( NbHIN1 ) gene and generated the transgenic tobacco overexpressing the NbHIN1 gene. In a subcellular localization experiment, we found that NbHIN1 localized in the plasma membrane and cytosol. Overexpression of NbHIN1 did not lead to observed phenotype compared to wild type tobacco plant. However, the NbHIN1 overexpressing tobacco plant exhibited significantly enhanced resistance to TMV infection. Moreover, RNA-sequencing revealed the transcriptomic profiling of NbHIN1 overexpression and highlighted the primary effects on the genes in the processes related to biosynthesis of amino acids, plant-pathogen interaction and RNA transport. We also found that overexpression of NbHIN1 highly induced the expression of NbRAB11, suggesting that jasmonic acid signaling pathway might be involved in TMV resistance. Taken together, for the first time we demonstrated that overexpressing a pathogenesis-related gene NbHIN1 in N. benthamiana significantly enhances the TMV resistance, providing a potential mechanism that will enable us to engineer tobacco with improved TMV resistance in the future.